Development of a Family-Centered Hypertension Education Module to Prevent Cardiovascular Complications in Community Settings - Emiliasari, Dian; Wisuda, Aris Citra; Suraya, Citra (Yayasan Rumah Ilmu Professor, 2025)
Hypertension is a major risk factor for cardiovascular complications and remains a prevalent public health concern, particularly in community settings. Family involvement plays a vital role in supporting lifestyle modifications and treatment adherence. However, educational tools tailored to family support in hypertension management are still limited. This study aimed to develop a family-centered hypertension education module designed to enhance knowledge, promote behavioral changes, and prevent cardiovascular complications among hypertensive patients in the community. A research and development (R&D) design was employed using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The study was conducted at Puskesmas (Community Health Center) 23 Ilir Palembang from May to June 2025. Data were collected through interviews, expert validation, and pre-post tests involving 30 families of hypertensive patients. Validation involved a panel of experts in nursing, cardiology, and health education. Descriptive and paired t-test analyses were applied. The developed module consists of five core sections: understanding hypertension, healthy diet, physical activity, medication adherence, and family roles in disease management. Expert validation showed high content validity (CVI = 0.94). Post-intervention testing revealed a significant improvement in family knowledge and engagement (p < 0.05), indicating the module's effectiveness. The family-centered hypertension education module is feasible, valid, and effective in improving family support and awareness to prevent cardiovascular complications. Implementation of the module is recommended in community health centers to strengthen family involvement in hypertension management. Further research with larger samples and long-term follow-up is advised to evaluate its sustained impact.